Effectiveness Of Topical Sucralfate Ointment For Healing And Postoperative Pain Reduction After Milligan Morgan Hemorrhoidectomy - Rai, Saurabh; Soni, Sameer; Agrawal, Puneet (Journal of Neonatal Surgery, 2026)
Introduction: Hemorrhoids, characterized by symptomatic enlargement and displacement of anal cushions, pose a significant medical and socioeconomic challenge. Hemorrhoidectomy, particularly the Milligan-Morgan technique, remains a common surgical intervention for advanced cases. However, postoperative pain is a notable complication, often leading to prolonged hospital stays. This study aimed to assess the role of topical sucralfate ointment in reducing postoperative pain and enhancing healing following open hemorrhoidectomy. Methods: The study included 80 patients with third- and fourth-degree hemorrhoids undergoing Milligan-Morgan hemorrhoidectomy. Patients were randomly assigned to receive either topical 10% sucralfate cream (n=40) or a placebo (n=40). Postoperatively, both groups followed a standard care regimen. Demographic profile, postoperative pain, and healing, along with pain during defecation, were analyzed respectively. Results: The sucralfate group exhibited significantly lower pain scores at postoperative days 1, 7, 14, and 28 compared to the placebo group. Wound healing was notably better in the sucralfate group, with 90% achieving complete healing compared to 60% in the placebo group on day 28. Additionally, pain during defecation was significantly lower in the sucralfate group at 1 and 2 weeks postoperatively. Conclusion: Topical sucralfate demonstrates effectiveness in reducing acute postoperative pain and promoting wound healing following Milligan-Morgan hemorrhoidectomy. Despite study limitations, these findings highlight the potential of sucralfate as a valuable adjunct in post-hemorrhoidectomy care. Further research is recommended to refine randomization techniques and explore variations in sucralfate cream strength and dosage...